FLUTUAÇÃO POPULACIONAL DOS PRINCIPAIS NOCTUÍDEOS E DISTRIBUIÇÃO VERTICAL DE OVOS E LARVAS NA CULTURA DA SOJA - Wisch, Lucas Nataniel (2011)
Soybean is one of the main oleaginous crop produced in Brazil. Studies on populational dynamic and immature stage vertical distribution in soybean canopy are very important to improve technology application and control timing. We studied population dynamics and vertical distribution of eggs and larvae of the velvetbean caterpillar, Anticarsia gemmatalis and two Plusiinae species, during the cycle of two soybean cultivars of different growth habits in three sowing dates. Experiments were conducted on Coodetec 206 and BMX Potência RR cultivars during the 2010/2011 growing season in Ponta Grossa, Paraná state. Samples were collected through the crop cycle. Eggs and caterpillars from each third of the plant (bottom, middle and upper) and on different plant structures (main stem, branches, pods and adaxial or abaxial surfaces of leaves) were quantified. Data were analyzed using descriptive statistics and nonparametric Kruskal-Wallis analysis. Plusiinae species occurred simultaneously with A. gemmatalis, which was the predominant species. Highest densities of eggs and larvae of A. gemmatalis were recorded during the second half of January and February. In February we observed the highest densities of Plusiinae. Through the late sowing season we recorded the highest densities of immature stages of Noctuidae. The highest eggs densities for A. gemmatalis and Plusiinae occurred in the middle third (44.03% and 45.99%, respectively) of the canopy followed by the lower (31.96% and 34.18%) and upper portion (24.01% e 19.83%). Small larvae of A. gemmatalis were found mainly in middle (44.08%) and lower third of the plant (36.97%), while medium larvae occurred in higher density in the middle (42.86%) and upper (41.90%) stratum. Meanwhile, most of the large larvae are found in the upper portion of the canopy (63.41%). Highest densities of small, medium and large Plusiinae larvae, we found in middle (43.37%, 44.63% e 44.83%, respectively) and lower (49.46%, 31.40% e 31.03%) third of the canopy. Eggs and caterpillars were found mainly on the abaxial surface of leaflets.